Information needs and information seeking behaviour of students utilizing electronic resources at the Library of UiTM Section 17, Shah Alam / Junaida Kamarudin - Kamarudin, Junaida (2001)
Students are increasingly expected to use electronic resources while at University. This study was undertaken to discover the information needs and the information-seeking behaviour of students utilizing the electronic resources at the Library of UiTM, Section 17, Shah Alam. It was to determine the level of use of this type of resource, how students feel about various issues surrounding electronic resources and whether their knowledge and skills helps them in the utilisation of the electronic services provided by the library. A questionnaire survey was used for this study. Data were gathered from 180 students from various programmes who came to register at the Information Service Department where these electronic resources are placed. The data resulting from this survey revealed that within the survey population several significant relationships existed between major, gender, semester, year of respondents and the search strategies they employed as well as the ways they approached the electronic resources to search for information and the library that provides the service. Some of the findings were consistent with earlier studies; others reflected unanticipated trends in the information-seeking behaviour of the students. The findings also indicate that guidance in the use of electronic resources is necessary to help students meet some of their information requirements. Based on these findings, it was recommended that a more aggressive user education programmes should be developed and to propose an Information Literacy Course to be offer to students. This study updates the literature of the subject and may help the library of UiTM Section 17 to improve the electronic services to the students.